Comparison on diversity of terrestrial pteridophytes at disturbed and undisturbed area in Kuala Pilah, Negeri Sembilan / Nordiyana Mohd Nasir - Mohd Nasir, Nordiyana (Faculty of Applied Sciences, 2014)
This study of terrestrial pteridophytes at disturbed and undisturbed area in Kuala Pilah, Negeri Sembilan is aim to compare terrestrial pteridophytes species occurrence at two different sites in Kampung Beting Kuala Pilah and UiTM Negeri Sembilan Forest Reserve and to determine the diversity of terrestrial pteridophytes species. The method used at both sites is systematic square quadrate plots sampling. 11 terrestrial pteridophytes family were found at Site A (Disturbed Area) and Site B (Undisturbed Area) are Adiantaceae, Blechnaceae, Gleichniaceae, Hypopelidaceae, Pteridaceae, Lycopediceae, Nephrolepidaceae, Tectariaceae, Thelyptridaceae, Selaginellaceae and Schizaceae. There were 790 individuals with 10 species recorded at Site A and 1378 individuals with 15 species at Site B. Thelyptridaceae is found to be the majority species in Site A whereas Nephrolepidaceae contributes the largest percentage of existence in Site B.By using Shannon-Weiner Diversity Index, Site B had shown more diverse(H’=2.22). In term of species richness and species evenness, Site B also had befound more species richness (R1=5.17) by using Margalef `s Richness Index andmore even species (E=0.31) by using Evenness Index whereas Site A showed lessspecies diverse (H’=1.85), less species richness (R1=3.91) and less species even(E=0.24).